A high precision write/read circuits for memristors using digital input/output interfaces. (February 2020) - Daoud, Ahmad A.; Dessouki, Ahmed S.; Mostafa, Hassan; Abdallah, Rania M.; El-Rabaie, El-Sayed M.
Abstract: In this paper, high precision write and read circuits for memristors are proposed. The proposed write circuit utilizes a DC voltage provided by a Digital-to-Analog Converter (DAC) to tune the memristor to a specific memristance. A feedback link is connected to read the final memristance, and determine the required decision of switching the memristance to a lower or a higher memristance value. An Analog-to-Digital Converter (ADC) is used in the read circuit to convert the read voltage to a digital word. Simulations are carried out to test the proposed write and read circuits. Industrial hardware-calibrated TSMC 130 ​nm CMOS technology models are used in Cadence Spectre environment simulation tool throughout all the simulations.